Hydrogen Nanometrology in Advanced Carbon Nanomaterial Electrodes - Rui Lobo; Noe Alvarez; Vesselin Shanov (Nanomaterials, 2021)
A comparative experimental study between advanced carbon nanostructured electrodes, in similar hydrogen uptake/desorption conditions, is investigated making use of the recent molecular beam-thermal desorption spectrometry. This technique is used for monitoring hydrogen uptake and release from different carbon electrocatalysts: 3D-graphene, single-walled carbon nanotube networks, multi-walled carbon nanotube networks, and carbon nanotube thread. It allows an accurate determination of the hydrogen mass absorbed in electrodes made from these materials, with significant enhancement in the signal-to-noise ratio for trace hydrogen avoiding recourse to ultra-high vacuum procedures. The hydrogen mass spectra account for the enhanced surface capability for hydrogen adsorption in the different types of electrode in similar uptake conditions, and confirm their enhanced hydrogen storage capacity, pointing to a great potential of carbon nanotube threads in replacing the heavier metals or metal alloys as hydrogen storage media.